The Gondwana connections of northern Patagonia - Pankhurst, R. J. (2014)
A multidisciplinary study (U–Pb sensitive high-resolution ion microprobe geochronology, Hf and O isotopes in zircon, Sr and Nd isotopes in whole-rocks, as well as major and trace element geochemistry) has been carried out on granitoid samples from the area west of Valcheta, North Patagonian Massif, Argentina. These confirm the Cambrian age of the Tardugno Granodiorite (528 ± 4 Ma) and the Late Permian age of granites in the central part of the Yaminué complex (250 Ma). Together with petrological and structural information for the area, we consider a previously suggested idea that the Cambrian and Ordovician granites of northeastern Patagonia represent continuation of the Pampean and Famatinian orogenic belts of the Sierras Pampeanas, respectively. Our interpretation does not support the hypothesis that Patagonia was accreted in Late Palaeozoic times as a far-travelled terrane, originating in the Central Transantarctic Mountains, and the arguments for and against this idea are reviewed. A parautochthonous origin is preferred with no major ocean closure between the North Patagonian Massif and the Sierra de la Ventana fold belt.